The paleotectonic evolution of the western Mediterranean: provenance insights from the internal Betics, southern Spain - Poulaki, Eirini M.; Stockli, Daniel F. (Frontiers in Earth Science, 2022)
Since the early Cenozoic, the closure of the Alpine Tethys in the Western Mediterranean has been accomplished by protracted subduction, followed by collision and orogenic collapse. The internal zones of the Betic Cordillera (southern Spain) and Rif (northern Morocco) experienced subduction metamorphism and subsequent exhumation due to westward migration of the orogenic system. The detrital provenance of these meta-sedimentary units contains crucial insights into their pre-subduction stratigraphic arrangement, which is essential to constrain the pre-Cenozoic paleogeography and tectonic evolution of the Western Mediterranean. This study focuses on the Nevado-Filábride Complex (NFC) and the Eastern Alpujárride Complex in the Internal Betic Cordillera. New depth-profile zircon U-Pb LA-ICP-MS data from the NFC (N=72) and Alpujárride (N=21) and in-situ apatite U-Pb data from a metabasite within the NFC allow us to establish the pre-subduction stratigraphy, sedimentary provenance, and paleotectonic configuration of the Iberian rifted margin during the Paleozoic-Early Mesozoic. Our dataset demonstrates that the NFC represents an intact Devonian to Early Jurassic stratigraphic sequence that records the evolution of the Western Mediterranean from the Variscan orogeny to rifting and opening of the Alpine Tethys. Detrital zircon U-Pb age modes of the NFC remain remarkably similar for over 200 Myr with only the differences being the progressive addition of new zircon modes related to depositional ages. Additionally, comparison between the provenance record of the NFC and Alpujárride reveal notably similar zircon signatures of Carboniferous and Permian strata. This study reports the first data from the Triassic-Jurassic strata that record the opening of the Alpine Tethys. Additional evidence for rifting is present in the metabasites from the Veleta unit yielding in-situ apatite U-Pb ages of 197 Ma, recording CAMP magmatism and Early Jurassic rifting in the Alpine Tethys. The data demonstrate a palinspastic connection between the NFC and the Alpujárride. Based on these extensive new provenance data, we propose a pre-subduction tectonic configuration in which the NFC and Alpujárride both represent adjacent attenuated continental fragments that separated from the southern Iberian rifted margin by a narrow oceanic domain of the Alpine Tethys in the early Mesozoic.